The Effects of Teacher-Written Direct vs. Indirect Feedback on Students' Writing. (24th June 2015) - Jamalinesari, Ali; Rahimi, Farahnaz; Gowhary, Hsbib; Azizifar, Akbar
Abstract: This study investigated the effectiveness and efficacy of teacher's direct vs. indirect feedback on students' composition writings in an EFL context. Two classes (each class 10 students) of female intermediate students in a private English language learning institute were given writing assignments for ten class sessions. The students in every class provided with either direct or indirect feedback. The results were recorded and later analyzed. The data revealed that the class with indirect feedback improved better compared to the class with direct feedback. Moreover, the study has insights and implications for teachers.